Practice guideline summary: Treatment of restless legs syndrome in adults: Report of the Guideline Development, Dissemination, and Implementation Subcommittee of the American Academy of Neurology. (13th December 2016) - Winkelman, John W.; Armstrong, Melissa J.; Allen, Richard P.; Chaudhuri, K. Ray; Ondo, William; Trenkwalder, Claudia; Zee, Phyllis C.; Gronseth, Gary S.; Gloss, David; Zesiewicz, Theresa
Abstract : Objective: To make evidence-based recommendations regarding restless legs syndrome (RLS) management in adults. Methods: Articles were classified per the 2004 American Academy of Neurology evidence rating scheme. Recommendations were tied to evidence strength. Results and recommendations: In moderate to severe primary RLS, clinicians should consider prescribing medication to reduce RLS symptoms. Strong evidence supports pramipexole, rotigotine, cabergoline, and gabapentin enacarbil use (Level A); moderate evidence supports ropinirole, pregabalin, and IV ferric carboxymaltose use (Level B). Clinicians may consider prescribing levodopa (Level C). Few head-to-head comparisons exist to suggest agents preferentially. Cabergoline is rarely used (cardiac valvulopathy risks). Augmentation risks with dopaminergic agents should be considered. When treating periodic limb movements of sleep, clinicians should consider prescribing ropinirole (Level A) or pramipexole, rotigotine, cabergoline, or pregabalin (Level B). For subjective sleep measures, clinicians should consider prescribing cabergoline or gabapentin enacarbil (Level A), or ropinirole, pramipexole, rotigotine, or pregabalin (Level B). For patients failing other treatments for RLS symptoms, clinicians may consider prescribing prolonged-release oxycodone/naloxone where available (Level C). In patients with RLS with ferritin ≤75 μg/L, clinicians should consider prescribing ferrous sulfate with vitamin C (Level B). When nonpharmacologic approaches are desired, clinicians should consider prescribing pneumatic compression (Level B) and may consider prescribing near-infrared spectroscopy or transcranial magnetic stimulation (Level C). Clinicians may consider prescribing vibrating pads to improve subjective sleep (Level C). In patients on hemodialysis with secondary RLS, clinicians should consider prescribing vitamin C and E supplementation (Level B) and may consider prescribing ropinirole, levodopa, or exercise (Level C).